Experimental and numerical investigation on the behaviour of methane in supercritical conditions. (25th August 2016) - Ricci, Daniele; Natale, Pasquale; Battista, Francesco
Highlights: The supercritical and transcritical behaviour of methane is described. The turbulent flow in a narrow channel is experimentally and numerically studied. The channel is heated by a constant and uniform heat flux. The deterioration thermal performances is clearly observed at x / l  = 0.75–0.80. The numerical results are in good agreement with the experimental data. Abstract: The development of reliable cooling jackets covers a central role into successfully design and test a liquid rocket engine. In fact, very challenging operative conditions in terms of conjugated huge thermal and mechanical loads have to be dealt. Liquid rocket engines may be regeneratively cooled, such as the fuel is used also as a refrigerant in the cooling jackets. If a cryogenic fluid is used, the coolant may behave as a transcritical fluid: it may be injected as a liquid and, depending on the heat exchanged with the thrust chamber hot gases, may experience a phase pseudo-change; finally it comes out and is sent to the subsystem, located downstream, as a supercritical vapour. In this context, a deep comprehension of the methane behaviour in the cooling jacket operative conditions, particularly in the transcritical ones, is mandatory. In fact, most of the analyses, design methodologies and numerical procedures derive from the experiences gained in programs involving different kinds of cryogenic fuels. This paper focuses on the numerical rebuilding of the experimental investigation, performed by means of a specific test article, conceived and realized by CIRA. The breadboard, named MTP-BB (Methane Thermal Properties Breadboard), is provided with a rectangular-shaped single channel, characterized by dimensions, representative of typical rocket engine cooling channels. The test campaign was successfully accomplished by collecting significant data, considering inlet temperature and pressure values, ranging from about 120 K to 140 K, and from about 10.0 to 17.0 MPa, respectively. The dedicated numerical rebuilding activity has been performed by adopting three dimensional models, including inlet and outlet interfaces, and very low discrepancies with respect to experimental data were observed. Simulations enabled the description of the thermal stratification as well as the "thermal deterioration" of methane inside a cooling jacket-like channel at supercritical conditions.